Gas permeation and selectivity characteristics of PSf based nanocomposite membranes. (10th October 2019) - Swain, Suchhanda S.; Unnikrishnan, Lakshmi; Mohanty, Smita; Nayak, Sanjay K.
Abstract: This study highlights successful development and evaluates the characteristics of graphene-derived nanohybrids (SGO and RSGO) incorporated MMM systems. Pristine GO and modified SiO2 (mSiO2 ) based membranes have also been prepared to assay the established synergistic effect on the performance. FTIR and WCA studies were carried out to endorse the insertion of different nanofillers into the virgin PSf matrix. SEM with EDS and AFM were accomplished to substantiate the distribution and dispersion pattern of the fillers within the base matrix. From the mechanical analysis, 46% improved tensile strength was perceived for the hybrid MMM system containing SGO. Finally, the dexterity was documented by analyzing the permeation behavior of the prepared membranes towards the selected O2 /N2 gas pair. The hybrid PSf/SGO system displayed 605% and 801% higher permeabilities for O2 as compared to the parent counterparts: (PSf/mSiO2, PSf/GO), respectively. Meanwhile, PSf/RSGO membrane exhibited a slightly reduced performance than the former hybrid system. Graphical abstract: Image 1 Highlights: Evaluation of the influence of different fillers (mSiO2, GO, SGO, and RSGO) on the performance of PSf based membrane systems. The MMM containing SGO nanohybrid displayed an excellent tensile strength f 35% and 46% higher than the parent counterparts including PSf/mSiO2 and PSf/GO systems, respectively. The nanohybrid systems exhibited improved permeability coefficients (Pi ) and greater ideal selectivity factors for the chosen gas pair. The separation performance was surpassed the Robeson's upper bound trade-off limit.